Causal relationship of gut microbiota with diabetic nephropathy: a Mendelian randomization analysis - Yan, Wei; Ge, Ying; Wang, Lina; Wang, Yuntao; He, Daikun (Frontiers in Microbiology, 2024)
Background: Patients with DN (diabetic nephropathy) show remarkable variations in their gut microbiota composition. However, to date, no study has shown whether a causal relationship exists between gut microbiota composition and DN.Methods: Here, we performed a two-sample Mendelian randomization (MR) investigation for identifying causal associations of gut microbiota with DN. Gut microbiota genetic data were gathered from the recent genome-wide association study pooled data of the MiBioGen consortium, which included 24 cohorts and 18,340 individuals.Results: IVW(Inverse variance weighting) revealed that Verrucomicrobia (odds ratio